2018
DOI: 10.1039/c8ra06460a
|View full text |Cite
|
Sign up to set email alerts
|

Ethylenediamine mediated luminescence enhancement of pollutant derivatized carbon quantum dots for intracellular trinitrotoluene detection: soot to shine

Abstract: Vehicle-generated toxic pollutants are composed of gaseous smoke and particulate byproducts accumulated as a black substance at its exhaust.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“…Devi et al. [ 51 ] reported that a simple hydrothermal method to yield CQDs with an average size of 4.2 nm using soot as carbon source. The recycling of kitchen waste can reduce the amount of organic matter entering the landfill, reduce the generation of odor and landfill leachate, and avoid the adverse impact of excessive moisture on waste incineration.…”
Section: Carbon Source and Synthesis Methods Of Biomass Carbon Dotsmentioning
confidence: 99%
“…Devi et al. [ 51 ] reported that a simple hydrothermal method to yield CQDs with an average size of 4.2 nm using soot as carbon source. The recycling of kitchen waste can reduce the amount of organic matter entering the landfill, reduce the generation of odor and landfill leachate, and avoid the adverse impact of excessive moisture on waste incineration.…”
Section: Carbon Source and Synthesis Methods Of Biomass Carbon Dotsmentioning
confidence: 99%
“…[7][8][9][10] Due to the use of biomolecular precursors, the as-synthesized uorescent biodots are oen endowed with inherent biocompatibility, good aqueous solubility, chemical stability and inertness 11,12 suitable for a wide range of biomedical applications. [13][14][15][16] For example, uorescent biodots derived from long chain DNAs have been developed for metal ion sensing (e.g., Hg 2+ , Ag + , and Fe 2+ ), bioimaging and drug delivery. 11,12,[17][18][19] However, all these studies do not investigate the contribution of the four basic units of DNA (i.e., deoxyadenosine, deoxyguanosine, deoxythymidine and deoxycytidine nucleotides) to the formation of the resultant biodots, which are important to tailor the biodot properties for specic biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidative acid (H 3 PO 4 ) breaks down PGS into nanosized particles (GQD2) at high temperature (200 °C) and enhances the solubility due to attachment of oxygen functionalities on the edges. 43 The purpose of using diamine was to minimize the surface defects and yield great optical properties. 44 The removal of extra polymers needs more dialysis time (1 week) as compared to small organic molecules of amine solution (24 h), employed as passivation agents to functionalize GQDs.…”
Section: Resultsmentioning
confidence: 99%